The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1678-7757-2019-0720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of violet LED light on in-office bleaching protocols: a randomized controlled clinical trial

Abstract: Colorimetric evaluation was performed using a spectrophotometer (ΔE, ΔL, Δa, Δb) and a visual shade guide (ΔSGU). Calcium (Ca)/phosphorous (P) ratio was quantified in the enamel microbiopsies. Measurements were performed at baseline (T 0), after bleaching (T B) and in the 14-day follow-up (T 14). At each bleaching session, a visual scale determined the absolute risk (AR) and intensity of tooth sensitivity (TS). Data were evaluated by one-way (ΔE, Δa, ΔL, Δb), two-way repeated measures ANOVA (Ca/P ratio), and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 37 publications
4
30
1
14
Order By: Relevance
“…On the other hand, a clinical study evidenced a low capacity of violet light to promote a bleaching effect compared to 40% hydrogen peroxide (Kury et al, 2020). However, increased bleaching potential was found associating carbamide and hydrogen peroxide and LED (Kury et al 2020), corroborating our results. In our study, groups CL and CA were similar when another heat source was used.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, a clinical study evidenced a low capacity of violet light to promote a bleaching effect compared to 40% hydrogen peroxide (Kury et al, 2020). However, increased bleaching potential was found associating carbamide and hydrogen peroxide and LED (Kury et al 2020), corroborating our results. In our study, groups CL and CA were similar when another heat source was used.…”
Section: Resultssupporting
confidence: 90%
“…It is speculated that the short wavelength of violet light (405 nm) may present a photolytic effect, breaking same absorption spectrum pigments on enamel surface (Alshammery, 2019). On the other hand, a clinical study evidenced a low capacity of violet light to promote a bleaching effect compared to 40% hydrogen peroxide (Kury et al, 2020). However, increased bleaching potential was found associating carbamide and hydrogen peroxide and LED (Kury et al 2020), corroborating our results.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…25 In vivo evidence demonstrated that enamel properties are preserved after whitening with peroxide gels in the presence of human saliva and adhered pellicle. 26 Therefore, evidence-based research indicates that CP treatment is an effective and safe option for patients seeking dental whitening. 1 Because charcoal powder requires the act of brushing, this could mislead patients not to brush teeth with fluoridecontaining toothpastes.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo evidence demonstrated that enamel properties are preserved after whitening with peroxide gels in the presence of human saliva and adhered pellicle 26 . Therefore, evidence‐based research indicates that CP treatment is an effective and safe option for patients seeking dental whitening 1 .…”
Section: Discussionmentioning
confidence: 99%